Human intestinal epithelial cells can internalize luminal fungi via LC3-associated phagocytosis - Cohen-Kedar, Sarit; Shaham Barda, Efrat; Rabinowitz, Keren Masha; Keizer, Danielle; Abu-Taha, Hanan; Schwartz, Shoshana; Kaboub, Kawsar; Baram, Liran; Sadot, Eran; White, Ian; Wasserberg, Nir; Wolff-Bar, Meirav; et al. (Frontiers in Immunology, 2023)
Intestinal epithelial cells (IECs) are the first to encounter luminal microorganisms and actively participate in intestinal immunity. We reported that IECs express the β-glucan receptor Dectin-1, and respond to commensal fungi and β-glucans. In phagocytes, Dectin-1 mediates LC3 associated phagocytosis (LAP) utilizing autophagy components to process extracellular cargo. Dectin-1 can mediate phagocytosis of β-glucan-containing particles by non-phagocytic cells. We aimed to determine whether human IECs phagocytose β-glucan-containing fungal particles via LAP. Zymosan (β-glucan particle) and Heat-killed and UV inactivated C. albicans were phagocytosed by monolayers of human colonic (n=18) and ileal (n=4) organoids and IEC lines. LAP was identified by LC3 and Rubicon recruitment to phagosomes and lysosomal processing of internalized particles was demonstrated by co-localization with lysosomal dyes and LAMP2. Phagocytosis was significantly diminished by blockade of Dectin-1, actin polymerization and NAPDH oxidases. Our results show that human IECs sense luminal fungal particles and internalize them via LAP. This novel mechanism of luminal sampling suggests that IECs may contribute to the maintenance of mucosal tolerance towards commensal fungi.